PENINGKATAN KAPABILITAS MARKETING PELAKU USAHA MELALUI E-COMMERCE DAN DIGITAL PROMOTION DI KECAMATAN TLOGOWUNGU, KABUPATEN PATI - Setiadi, Teguh; Ilhami, Susanti Dwi; Kusumasari, Findi Citra; Slamet, Ayyub Hamdanu Budi Nurmana Mulyana; Darnis, Febriyanti; Kusumajaya, Robby Andika (Universitas Mataram, 2024)
E-commerce is a strong global trend driven by strengthening economic policies, changes in customer behavior and increased production in the form of technology. In carrying out community service by conducting direct observations using activity methods with data collection and direct assistance. Based on the capability perspective and market orientation literature, the activity model to determine the level of marketing that SME products are promoted by developing and producing a marketplace using e-commerce as a sales channel, one of which is on Instagram, Facebook or YouTube. One of the obstacles faced by business actors shows that the required online marketing capabilities are still insufficient to increase sales in digital form. In the end, community service resulted in online marketing having more efficiency, which was reflected in a market-based and market-driven approach, playing an important role in increasing the influence of online marketing capabilities. The conclusion in community service is that the results of assistance to produce e-commerce in the form of training to promote products can increase promotional value by up to 98%. The value can be obtained for the use of social media as well as promoting online shops so that it can increase the market share of SME business actors. In the activities that will be carried out in the next service, we can further improve the facilities and infrastructure of the service event to further support the success of the service event considering partners in this case for service activities for small and medium enterprises (UKM).